INOVASI LAYANAN DIGITAL PAK DALMAN SEBAGAI UPAYA TRANSFORMASI HUKUM PELAYANAN PUBLIK UNTUK MEWUJUDKAN EFISIENSI DAN AKUNTABILITAS PENCATATAN SIPIL DI KABUPATEN KENDAL - Rahma, Laela Novitri Ervia (FKPH Universitas Brawijaya, 2024)
The digital service innovation PAK DALMAN, implemented by the Dispendukcapil of Kendal Regency, is a strategic step in supporting the transformation of public service law, particularly in population administration. PAK DALMAN enables citizens to apply for civil documents such as electronic ID cards, Family Cards (KK), birth certificates, and relocation certificates daring without having to visit service offices. This study employs a participatory observation method, where the author directly serves as a PAK DALMAN agent, along with a literature review of relevant regulations, such as Law No. 25 of 2009 and Ministerial Regulation No. 7 of 2019. The findings show that PAK DALMAN enhances efficiency and accountability in civil administration services. However, challenges related to digital literacy among citizens and infrastructure readiness remain significant barriers. Therefore, increased socialization and digital literacy efforts are needed, especially for communities unfamiliar with technology. By addressing these issues, PAK DALMAN can serve as a more inclusive and effective public service model in the long term.